Postoperative hemorrhage caused by portal hypertension associated with autoimmune pancreatitis: A case report. Issue 8 (February 2018) - Wang, Puzi; Xie, Rongli; Zhao, Zhifeng; Ren, Jiajun; Fei, Jian
Abstract: Rationale: Autoimmune pancreatitis is a form of chronic pancreatitis, characterized by diffused enlargement of the pancreas and irregular narrowing of the main pancreatic duct. The theory that portal hypertension is associated with autoimmune pancreatitis has not been emphasized. In addition, only a few studies report that the gastrointestinal tract hemorrhage caused by portal hypertension is associated with autoimmune pancreatitis. Patient concerns: The patient was a 61-year-old male with pancreas occupying lesion detected in a physical examination. Preoperative CT showed portal vein diameter increased significantly (1.6 cm) and the junction of splenic and portal vein was capsuled by lesions and the splenic vein became thin. The Whippie procedure was performed for the correction of the lesion. The pancreatic tissue showed chronic inflammation and lymphocytic infiltration and fibrosis, and abundant IgG4 + cells. After the surgery, the patient suffered twice from postoperative hemorrhage (9 and 16 mos). Diagnoses: Postoperative hemorrhage, autoimmune pancreatitis. Intervention: Electronic gastroscopy, exploratory laparotomy, and titanium clips were used simultaneously to stop the bleeding. Outcomes: The patient recovered well after the surgery. Lessons: In this study, we present the case of repeated postoperative hemorrhage (9 and 16 mos). We discussed the correlation between postoperative hemorrhage and autoimmune pancreatitis, and the cause of postoperative hemorrhage.